Daily Intermittent Normobaric Hypoxia Over 2 Weeks Reduces BDNF Plasma Levels in Young Adults – A Randomized Controlled Feasibility Study - Becke, Andreas; Müller, Patrick; Dordevic, Milos; Lessmann, Volkmar; Brigadski, Tanja; Müller, Notger G. (Frontiers in Physiology, 2018)
Background: The results from animal and human research indicate that acute intermittent hypoxia can enhance brain-derived neurotrophic factor (BDNF) plasma levels and gene expression. As BDNF is known to promote the differentiation of new neurons and the formation of synapses, it has been proposed to mediate adult neuroplasticity. Thus, the present study aimed to analyze the long-term effects of daily intermittent exposure to normobaric hypoxia (simulating high altitude exposure at approximately 4000–5000 m) over 2 weeks on BDNF levels in young adults. Methods: Twenty-eight young adults (age: 19–33 years) were randomized into a hypoxic intervention group (N = 14) or the control group (N = 14). Participants in the intervention group breathed intermittent normobaric hypoxic air at resting conditions (5 min intervals, 80–85% SpO2 measured via a finger pulse oximeter, 12 sessions for 60 min/day for 2 weeks) via a hypoxic generator. BDNF plasma and serum levels were determined at baseline and at 2 weeks after intervention using sandwich ELISAs. Results: After 2 weeks of daily intermittent hypoxic treatment (IHT), we found a significant group x time interaction effect for BDNF plasma levels based on a significant decrease in BDNF levels in the hypoxia group. Conclusion: Our results demonstrate that daily intermittent administration of hypoxic air has a significant effect on BDNF regulation in healthy young adults. Contrary to other results reporting an increase in BDNF levels under hypoxic conditions, the present data suggest that hypoxic treatment using intensive IHT can reduce BDNF plasma levels for at least 2 weeks. This finding indicates that the daily application of hypoxic air is too frequent for the aimed physiological response, namely, an increase in BDNF levels.